2014
DOI: 10.1002/ijc.29207
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric factors and ovarian cancer risk: A systematic review and nonlinear dose‐response meta‐analysis of prospective studies

Abstract: the evidence relating body fatness to ovarian cancer risk was considered inconclusive, while the evidence supported a probably causal relationship between adult attained height and increased risk. Several additional cohort studies have since been published, and therefore we conducted an updated meta-analysis of the evidence as part of the Continuous Update Project. We searched PubMed and several other databases up to 20th of August 2014. Summary relative risks (RRs) were calculated using a random effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 62 publications
7
70
0
Order By: Relevance
“…Previous studies of weight gain in adult solid tumors have shown an increased risk associated with weight gain in adulthood [21, 3638]. The evidence for an association between weight gain and leukemia is not as well established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of weight gain in adult solid tumors have shown an increased risk associated with weight gain in adulthood [21, 3638]. The evidence for an association between weight gain and leukemia is not as well established.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic overlap with diabetes appeared mainly in association with mucinous EOC. Overall, the directions of association are consistent with what has been reported in observational studies [170][171][172][173], although most of these associations are not significant.…”
Section: Genetic Overlap Of Eoc Subtypes and Associated Environmentalsupporting
confidence: 88%
“…So far epidemiological and genetic studies have identified many lifestyle, environmental and genetic factors associated to an increase in risk of EOC. Among these, smoking [169,170], obesity [171][172][173], and type 2 diabetes [174,175] are associated with an increased risk, while [later] age at menarche appears to confer some protection [176]. Studies have identified multiple subtype specific and nonspecific genetic variants (e.g.…”
Section: Epithelial Ovarian Cancermentioning
confidence: 99%
See 2 more Smart Citations